A soft board electrolytic copper foil and a preparation method and application thereof
Patent Information
- Application Number
- CN202611312144.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]为此,本发明所要解决的技术问题在于克服现有技术中软板用极薄铜箔延伸率低、耐弯折性差、与柔性基材结合力不足、抗拉强度与延伸率难以兼顾的问题,从而提供了高延伸率软板电解铜箔
本发明通过复合添加剂协同调控铜电沉积行为,晶粒细小均匀,抑制再结晶,5.0-9.0μm厚度下抗拉强度不小于380 MPa,延伸率不小于12%,满足FPC反复弯折、拉伸的高挠曲要求。同时,本发明采用专用粗化-固化工艺使铜箔表面粗糙度适中、晶粒均匀,兼顾精细线路蚀刻精度与PI基材贴合强度,不易分层、起泡。本发明的偶联剂涂覆显著提升抗氧化性、耐化学性与耐弯折性,延长FPC使用寿命。本发明流程简洁、操作稳定,适合连续化生产,所制铜箔适配高端柔性印制电路板批量应用。
Smart Images

Figure CN122959818A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrolytic copper foil preparation technology, and in particular to an electrolytic copper foil for flexible printed circuit boards, its preparation method, and its application. Background Technology
[0002] Electrolytic copper foil is a key basic material in the electronic information industry and is widely used in the manufacture of various printed circuit boards. Flexible printed circuit boards (FPCs), as the core carrier for the thinning, flexibility and high-density integration of electronic devices, place extremely high performance requirements on the matching electrolytic copper foil.
[0003] Copper foil for flexible printed circuit boards (FPCs) needs to withstand dynamic mechanical loads such as bending, curling, and stretching over long periods, while also meeting the processing requirements of fine circuit etching and lamination. As FPCs develop towards ultra-thin, highly flexible, and highly reliable designs, the thickness of copper foil continues to decrease, and more stringent standards are being imposed on indicators such as elongation, tensile strength, bending resistance, surface adhesion, and dimensional stability.
[0004] Currently, there are technical bottlenecks in ultra-thin copper foil (thickness ≤ 9μm) for flexible printed circuit boards (FPCs). For example, reducing the thickness increases the internal stress of the copper foil, making it prone to recrystallization, resulting in insufficient elongation and easy breakage after repeated bending, which cannot meet the requirements for high-flexibility FPCs. Traditional additive systems are difficult to achieve synergistic control of grain refinement and mechanical properties, making it difficult to balance tensile strength and elongation. The surface properties of the copper foil and its adhesion to the FPC substrate (such as polyimide PI) are insufficient, easily leading to delamination and blistering. It also has poor chemical resistance and oxidation resistance, affecting the yield and service life of FPCs.
[0005] Existing technologies mostly focus on lithium-ion battery copper foil, with few specialized preparation techniques for FPC (Flexible Printed Circuit) copper foil. Furthermore, existing technologies suffer from low elongation, insufficient bending resistance, and complex processes, failing to meet the industrialization needs of high-end flexible circuit boards. Therefore, developing a simple, high-performance, high-elongation electrolytic copper foil preparation method for flexible circuit boards has significant market value. Summary of the Invention
[0006] Therefore, the technical problem to be solved by the present invention is to overcome the problems of low elongation, poor bending resistance, insufficient bonding force with flexible substrate, and difficulty in balancing tensile strength and elongation of ultra-thin copper foil for flexible circuit boards in the prior art, thereby providing high elongation electrolytic copper foil for flexible circuit boards.
[0007] To solve the above-mentioned technical problems, the present invention provides a method for preparing electrolytic copper foil for flexible printed circuit boards, comprising the following steps: S11: Add the aqueous solution of the composite additive to an aqueous solution containing copper ions to form a copper ion electrolyte; the aqueous solution of the composite additive includes 3-15 mg / L of collagen, 5-50 mg / L of polyethylene glycol (molecular weight 2000-8000), 0.5-10 mg / L of polyethyleneimine (molecular weight 600-1800), and 0.1-3 mg / L of 2-mercaptobenzimidazole; S12: Obtain a green foil by electrolytic deposition using the copper ion electrolyte; S13: The raw foil is surface treated and coated with a coupling agent to obtain the electrolytic copper foil for flexible circuit boards.
[0008] Preferably, the volume ratio of the composite additive aqueous solution to the copper ion-containing aqueous solution is 1:800-1500.
[0009] Preferably, the aqueous solution containing copper ions comprises 95-130 g / L of copper ions and 90-120 g / L of SO4. 2- And 10-35 mg / L of chloride ions. Chloride ions are a basic additive, and their concentration does not need to be too high; if it is too high, normal production will not be possible.
[0010] Furthermore, the chloride ions are obtained by adding hydrochloric acid.
[0011] Preferably, in step S12, the temperature of the copper ion electrolyte during electrolytic deposition is 45-55℃, and the electrolytic deposition time is 2-4 minutes. This temperature range can improve the copper ion diffusion rate, reduce concentration polarization, and produce a fine and smooth coating grain, balancing the strength and elongation of the copper foil. The moderate temperature avoids high-temperature failure of additives and coarse grains. Short deposition time makes it easier to control foil thickness, reduce hydrogen evolution, pinholes, and dendrite defects, improve production efficiency, and produce a uniform and dense coating, balancing quality and production capacity.
[0012] Preferably, in step S12, the cathode current density is 45-70 A / dm³. 2 The anode current density is the same.
[0013] Furthermore, the cathode current density is 50-65 A / dm³. 2 .
[0014] Preferably, in step S12, the thickness of the green foil is 5-9 μm. Ultra-thin green foil meets the high energy density requirements of lithium batteries, increasing the amount of active material coated on the electrode and improving battery capacity. The thin foil reduces the overall weight and volume of the battery cell, thus increasing energy density. Simultaneously, it maintains mechanical strength, is not easily broken, meets the requirements of high-speed coating and rolling processing, aligns with the lightweight development trend of power batteries, and balances energy storage performance with processing yield.
[0015] Preferably, in step S13, the surface treatment steps include pickling, roughening, curing, ashing, and passivation.
[0016] Furthermore, the roughening treatment employs electroplating, including the use of 15-30 g / L copper ions and 120-160 g / L SO4. 2- The treatment solution, roughening temperature is 25-35℃, and current density is 30-50 A / dm³. 2 The processing time is 5-10 seconds, and the coarsened grains are uniform and fine, making it suitable for fine etching of FPC.
[0017] Furthermore, the curing process employs direct current electrodeposition electroplating, including the use of 45-65 g / L copper ions and 80-110 g / L SO4. 2- The treatment solution is used, the curing temperature is 45-55℃, and the current density is 40-60 A / dm³. 2 Processing time is 5-10 seconds.
[0018] Preferably, in step S13, the coupling agent is an aqueous solution of one or both of γ-aminopropyltriethoxysilane (KH-550) and γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560).
[0019] Preferably, in step S13, the concentration of the coupling agent is 300-1500 mg / L.
[0020] Preferably, in step S13, after the coupling agent is coated, it is dried and wound up at 100-180°C to improve the bonding force with the polyimide (PI) flexible substrate.
[0021] The present invention also provides an electrolytic copper foil for flexible printed circuit boards prepared by the above preparation method.
[0022] This invention also provides a flexible printed circuit board, prepared using the aforementioned electrolytic copper foil for flexible circuit boards. The flexible printed circuit board is a bendable circuit board made of a flexible insulating substrate, capable of being bent and fitted to irregularly shaped devices. The electrolytic copper foil for flexible circuit boards has excellent ductility, is thin and flexible, and is not easily cracked or broken when bent; its dense grains provide stable conductivity, making it suitable for repeated bending conditions of flexible circuit boards. Its ultra-thin specifications are adapted to lightweight designs, balancing conductivity and bending fatigue resistance to ensure long-term circuit reliability.
[0023] Compared with the prior art, the above-described technical solution of the present invention has the following advantages: This invention utilizes composite additives to synergistically regulate copper electrodeposition behavior, resulting in fine and uniform grains that inhibit recrystallization. At a thickness of 5.0-9.0 μm, the tensile strength is no less than 380 MPa, and the elongation is no less than 12%, meeting the high flexibility requirements of FPCs under repeated bending and stretching. Simultaneously, this invention employs a dedicated roughening-curing process to achieve moderate surface roughness and uniform grains in the copper foil, balancing the precision of fine circuit etching with the bonding strength to the PI substrate, and minimizing delamination and blistering. The coupling agent coating significantly enhances oxidation resistance, chemical resistance, and bending resistance, extending the lifespan of the FPC. This invention features a simple process, stable operation, and is suitable for continuous production; the produced copper foil is suitable for mass production applications of high-end flexible printed circuit boards. Attached Figure Description
[0024] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings.
[0025] Figure 1 This is a process flow diagram of the present invention; Figure 2 This is a scanning electron microscope (SEM) image of the copper foil of this invention. Detailed Implementation
[0026] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.
[0027] Example 1: Preparation of copper foil for flexible printed circuit boards An electrolyte was prepared by reacting high-purity copper wire (99.98%) with 98 wt% concentrated sulfuric acid in air, resulting in an electrolyte containing Cu. 2+ 100g / L, SO4 2- 115 g / L, Cl - 25 mg / L of water at a temperature of 52°C.
[0028] The compound additives consist of 8 mg / L collagen (average molecular weight 4000), 20 mg / L polyethylene glycol (average molecular weight 4000), 2 mg / L polyethyleneimine (average molecular weight 1200), and 0.5 mg / L 2-mercaptobenzimidazole.
[0029] The composite additive aqueous solution and electrolyte were added to the electrolyte at a volume ratio of 1:1000, with a current density of 55 A / dm³. 2 Electrodeposition time was 3 min, followed by polishing to obtain a green foil with a thickness of 9.0 μm.
[0030] The subsequent surface treatment steps for the raw foil are as follows: 1. Pickling: This process removes the oxide layer and passivation film from the copper foil surface, activates the surface lattice, and improves the adhesion of subsequent roughening and alloying layers. The pickling solution is 200 g / L sulfuric acid, and the temperature is 35℃.
[0031] 2. Flexible Circuit Board (FPCB) Specific Roughening: Nanoscale copper granules are deposited on the rough surface of the copper foil, significantly improving the mechanical bonding strength between the copper foil and the copper-clad laminate. The roughening solution system contains 20 g / L Cu ions and SO42-. 2- 140 g / L, temperature 30℃, current density 35 A / dm 2 Electrodeposition time: 8s.
[0032] 3. Water Wash 1: Rinse the copper foil surface to remove acid residue and impurities, preventing cross-contamination of subsequent solutions and ensuring the purity of the copper foil surface. Use ultrapure water with a conductivity of <5 μS / cm for rinsing.
[0033] 4. Curing: The rough, loose copper layer is cured and encapsulated, depositing a dense copper layer to fix the loose copper buds and prevent them from detaching. The curing solution system contains 55 g / L Cu ions and SO42-. 2- 100 g / L, temperature 48℃, current density 50 A / dm 2 Electrodeposition time: 8 s.
[0034] 5. Water Wash 2: Rinse the copper foil surface to remove acid residue and impurities, prevent cross-contamination of subsequent solutions, and ensure the purity of the copper foil surface. Use ultrapure water with a conductivity of <5μS / cm for water washing.
[0035] 6: Ashing: A zinc-nickel alloy layer is deposited on the surface of the cured layer to improve the heat resistance of the copper foil. The ashing plating solution system contains 2.7 g / L Zn ions, 1.65 g / L Ni ions, 90 g / L potassium pyrophosphate, pH 10.5, and temperature 38℃.
[0036] 7: Water washing 3: Rinse the copper foil surface to remove acid residue and impurities, prevent cross-contamination of subsequent solutions, and ensure the purity of the copper foil surface. Use ultrapure water with conductivity <5μS / cm for water washing.
[0037] 8. Passivation: A dense inorganic passivation film is formed on the surface of the copper foil, isolating it from air and moisture, significantly improving its oxidation and rust resistance during storage and transportation, and extending its shelf life. The passivation plating solution system has 1.4 g / L Cr ions, pH 11, and a temperature of 26℃.
[0038] 9: Water washing 4: Rinse the copper foil surface to remove acid residue and impurities, prevent cross-contamination of subsequent solutions, and ensure the purity of the copper foil surface. Use ultrapure water with conductivity <5μS / cm for water washing.
[0039] Coating the surface of the surface-treated copper foil with 1000 mg / L KH-550, drying at 125℃ and winding it up, yields copper foil for flexible circuit boards.
[0040] Example 2: Preparation of copper foil for flexible printed circuit boards An electrolyte was prepared by reacting high-purity copper wire (99.98%) with 98wt% concentrated sulfuric acid in air, resulting in an electrolyte containing Cu. 2+ 95g / L, SO4 2- 90 g / L, Cl - 10 mg / L of water at 45°C.
[0041] The compound additive consists of 3 mg / L collagen, 5 mg / L polyethylene glycol (average molecular weight 4000), 0.5 mg / L polyethyleneimine (average molecular weight 1200), and 0.1 mg / L 2-mercaptobenzimidazole.
[0042] The composite additive and electrolyte were added to the electrolyte at a volume ratio of 1:800, with a current density of 45 A / dm³. 2 Electrodeposition time was 2 min, followed by polishing to obtain a green foil with a thickness of 5 μm.
[0043] The subsequent surface treatment steps for the raw foil are as follows: 1. Pickling: Removes the oxide layer and passivation film from the surface of the raw foil, activates the surface lattice, and improves the adhesion of the subsequent roughening layer and alloy layer of the copper foil. The pickling solution is 180 g / L sulfuric acid, and the temperature is 30℃.
[0044] 2. Flexible Circuit Board (FPCB) Specific Roughening: Nanoscale copper granules are deposited on the rough surface of the copper foil, significantly improving the mechanical bonding strength between the copper foil and the copper-clad laminate. The roughening solution system contains 20 g / L Cu ions and SO42-. 2- 140 g / L, temperature 30℃, current density 35 A / dm 2 Electrodeposition time: 8s.
[0045] 3. Water Wash 1: Rinse the copper foil surface to remove acid residue and impurities, prevent cross-contamination of subsequent solutions, and ensure the purity of the copper foil surface. Use ultrapure water with conductivity <5μS / cm for water washing.
[0046] 4. Curing: The rough, loose copper layer is cured and encapsulated, depositing a dense copper layer to fix the loose copper buds and prevent them from detaching. The curing solution system contains 55 g / L Cu ions and SO42-. 2- 100 g / L, temperature 48℃, current density 50 A / dm 2 Electrodeposition time: 8 s.
[0047] 5. Water Wash 2: Rinse the copper foil surface to remove acid residue and impurities, prevent cross-contamination of subsequent solutions, and ensure the purity of the copper foil surface. Use ultrapure water with conductivity <5 μS / cm for water washing.
[0048] 6. Ashing: A zinc-nickel alloy layer is deposited on the surface of the cured layer to improve the heat resistance of the copper foil. The ashing plating solution system contains 2.7 g / L Zn ions, 1.65 g / L Ni ions, 90 g / L potassium pyrophosphate, pH 10.5, and temperature 38℃.
[0049] 7. Water Wash 3: Rinse the copper foil surface to remove acid residue and impurities, preventing cross-contamination of subsequent solutions and ensuring the purity of the copper foil surface. Use ultrapure water with a conductivity of <5 μS / cm for the water wash.
[0050] 8. Passivation: A dense inorganic passivation film is formed on the surface of the copper foil, isolating it from air and moisture, significantly improving its oxidation and rust resistance during storage and transportation, and extending its shelf life. The passivation plating solution system has 1.4 g / L of Cr ions, a pH of 11, and a temperature of 26℃.
[0051] 9. Water Wash 4: Rinse the copper foil surface to remove acid residue and impurities, preventing cross-contamination of subsequent solutions and ensuring the purity of the copper foil surface. Use ultrapure water with a conductivity of <5 μS / cm for rinsing.
[0052] Coating the surface of the surface-treated copper foil with 300 mg / L KH-550, drying at 100℃ and winding it up, yields copper foil for flexible circuit boards.
[0053] Example 3: Preparation of copper foil for flexible printed circuit boards An electrolyte was prepared by reacting high-purity copper wire (99.98%) with 98 wt% concentrated sulfuric acid in air, resulting in an electrolyte containing Cu. 2+ 130g / L, SO4 2- 120 g / L, Cl - 35 mg / L of water at a temperature of 55°C.
[0054] The compound additive consists of 15 mg / L collagen, 50 mg / L polyethylene glycol (average molecular weight 4000), 10 mg / L polyethyleneimine (average molecular weight 1200), and 3 mg / L 2-mercaptobenzimidazole.
[0055] The composite additive and electrolyte were added to the electrolyte at a volume ratio of 1:1500, with a current density of 70 A / dm³. 2 Electrodeposition time was 4 min, followed by polishing to obtain a green foil with a thickness of 9 μm.
[0056] The subsequent surface treatment steps for the raw foil are as follows: 1. Pickling: This process removes the oxide layer and passivation film from the copper foil surface, activates the surface lattice, and improves the adhesion of subsequent roughening and alloying layers. The pickling solution is 180 g / L sulfuric acid, and the temperature is 30℃.
[0057] 2. Flexible Circuit Board (FPCB) Specific Roughening: Nanoscale copper granules are deposited on the rough surface of the copper foil, significantly improving the mechanical bonding strength between the copper foil and the copper-clad laminate. The roughening solution system contains 20 g / L Cu ions and SO42-. 2- 140 g / L, temperature 30℃, current density 35 A / dm 2 Electrodeposition time: 8 s.
[0058] 3. Water Wash 1: Rinse the copper foil surface to remove acid residue and impurities, preventing cross-contamination of subsequent solutions and ensuring the purity of the copper foil surface. Use ultrapure water with a conductivity of <5μS / cm for rinsing.
[0059] 4. Curing: The rough, loose copper layer is cured and encapsulated, depositing a dense copper layer to fix the loose copper buds and prevent them from detaching. The curing solution system contains 55 g / L Cu ions and SO42-. 2- 100g / L, temperature 48℃, current density 50 A / dm 2 Electrodeposition time: 8s.
[0060] 5. Water Wash 2: Rinse the copper foil surface to remove acid residue and impurities, preventing cross-contamination of subsequent solutions and ensuring the purity of the copper foil surface. Use ultrapure water with a conductivity of <5 μS / cm for rinsing.
[0061] 6. Ashing: A zinc-nickel alloy layer is deposited on the surface of the cured layer to improve the heat resistance of the copper foil. The ashing plating solution system contains 2.7 g / L Zn ions, 1.65 g / L Ni ions, 90 g / L potassium pyrophosphate, pH 10.5, and temperature 38℃.
[0062] 7. Water Wash 3: Rinse the copper foil surface to remove acid residue and impurities, preventing cross-contamination of subsequent solutions and ensuring the purity of the copper foil surface. Use ultrapure water with a conductivity of <5 μS / cm for the water wash.
[0063] 8. Passivation: A dense inorganic passivation film is formed on the surface of the copper foil, isolating it from air and moisture, significantly improving its oxidation and rust resistance during storage and transportation, and extending its shelf life. The passivation plating solution system has 1.4 g / L Cr ions, pH 11, and a temperature of 26℃.
[0064] 9. Water Wash 4: Rinse the copper foil surface to remove acid residue and impurities, preventing cross-contamination of subsequent solutions and ensuring the purity of the copper foil surface. Use ultrapure water with a conductivity of <5 μS / cm for rinsing.
[0065] Coating the surface of the surface-treated copper foil with 1500 mg / L KH-550, drying at 180℃ and winding it up, yields copper foil for flexible circuit boards.
[0066] Comparative Example 1: Preparation of Copper Foil for Flexible Printed Circuit Boards This comparative example is the same as Example 1, except that the composite additive does not contain 2-mercaptobenzimidazole.
[0067] Comparative Example 2: Preparation of Copper Foil for Flexible Printed Circuit Boards This comparative example is the same as Example 1, except that the composite additive does not contain polyethyleneimine.
[0068] Comparative Example 3: Preparation of Copper Foil for Flexible Printed Circuit Boards This comparative example is the same as Example 1, except that the composite additive does not contain collagen.
[0069] Effect evaluation: The copper foil used in the flexible printed circuit board obtained in Example 1 was tested, and the testing standards and physical property test items are as follows: 1. Roughness: Tested according to the probe method in GB / T 29847-2025 Test Method for Copper Foil for Printed Circuit Boards, 6.6.
[0070] 2. Tensile strength and elongation: Tested on a tensile testing machine in accordance with 7.1 of GB / T 29847-2025 Test Method for Copper Foil for Printed Circuit Boards.
[0071] 3. Peel strength: Tested on a tensile testing machine in accordance with 7.4 of GB / T 29847-2025 Test Method for Copper Foil for Printed Circuit Boards.
[0072] 4. Antioxidant properties: Tested in accordance with GB / T 29847-2025 Test Methods for Copper Foil for Printed Circuit Boards, section 8.7, using a constant temperature oven that can provide 300℃.
[0073] 5. Bending resistance: Tested on a bending tester in accordance with 7.4 of GB / T 13557-2017 "Test Methods for Flexible Copper Clad Foil Materials for Printed Circuits".
[0074] The results of the physical property tests are shown in Table 1: Table 1 Performance test results of the examples and comparative examples
[0075] The results show that the copper foil for flexible printed circuit boards prepared by this invention has the following properties: thickness 9 μm, surface roughness Rz≤4.0, surface roughness Rz≤2.0, peel strength ≥1.2 N / mm, room temperature tensile strength ≥400 MPa, room temperature elongation ≥11%, bending resistance ≥5000 times, and oxidation resistance withstanding baking at 210℃ for 60 min without oxidation or discoloration.
[0076] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing electrolytic copper foil for flexible printed circuit boards, characterized in that, Includes the following steps: S11: Add the aqueous solution of the composite additive to an aqueous solution containing copper ions to form a copper ion electrolyte; the aqueous solution of the composite additive includes 3-15 mg / L of collagen, 5-50 mg / L of polyethylene glycol, 0.5-10 mg / L of polyethyleneimine and 0.1-3 mg / L of 2-mercaptobenzimidazole; S12: Electrolytic deposition is performed using the copper ion electrolyte to obtain a green foil; S13: The raw foil is surface treated and coated with a coupling agent to obtain the electrolytic copper foil for flexible circuit boards.
2. The preparation method according to claim 1, characterized in that: The volume ratio of the composite additive aqueous solution to the copper ion-containing aqueous solution is 1:800-1500.
3. The preparation method according to claim 1, characterized in that: The aqueous solution containing copper ions comprises 95-130 g / L of copper ions and 90-120 g / L of SO4. 2- And 10-35 mg / L of chloride ions.
4. The preparation method according to claim 1, characterized in that: In step S12, the temperature of the copper ion electrolyte during electrolytic deposition is 45-55℃, and the electrolytic deposition time is 2-4 minutes.
5. The preparation method according to claim 1, characterized in that: In step S12, the current density at the cathode is 45-70 A / dm². 2 .
6. The preparation method according to claim 1, characterized in that: In step S12, the thickness of the raw foil is 5-9 μm.
7. The preparation method according to claim 1, characterized in that: In step S13, the surface treatment steps include pickling, roughening, curing, ashing, and passivation.
8. The preparation method according to claim 1, characterized in that: In step S13, the coupling agent is an aqueous solution of one or both of γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
9. An electrolytic copper foil for flexible printed circuit boards prepared by the preparation method according to any one of claims 1-8.
10. A flexible printed circuit board, characterized in that, It is prepared using the electrolytic copper foil for flexible circuit boards as described in claim 9.